Food wars! : shokugeki no soma. 26, Second bout - Tsukuda, Yuto, 1989- (Shonen Jump advanced., 2018)
"Soma and the resistance have swept the first bout of the team shokugeki! But they can't rest on their laurels, as the second bout is soon to begin. With the Council of Ten's pride on the line, who will Central send out to protect it? And will Kuga's desire for a rematch with Tsukasa affect the lineup?"--Page [4] of cover.